The Thorny Problem of Translation and Interpreting Quality - Koby, Geoffrey S.; Lacruz, Isabel (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2018)
Judging quality in translation and interpreting and in the associated task of revision has a long and controversial history. We briefly comment on some aspects of this history to provide context for the contemporary perspectives on and investigations into quality assessment that are represented in this volume of Linguistica Antverpiensia, New Series: Themes in Translation Studies. A fundamental obstacle to progress is the lack of consensus about how to characterize high-quality translation or interpreting, let alone the identification of broadly accepted models for measuring translation or interpreting quality or the ability of translators or interpreters. The advent of machine translation and post-editing has focused attention on the very nature of quality: Is it proximity to a “gold standard” of perfection or is it characteristic of a product that simply serves its purpose well enough to satisfy the needs of the consumer? In other words, is quality something that should be measured and judged in absolute terms or in relative terms? Different philosophies of quality assessment reflect these dichotomies, with the absolutists seeking objective assessments based on detailed analyses of taxonomies of errors, whereas the relativists prefer a more holistic approach that is more sympathetic to subjective judgements. The contributors to this volume present a broad range of approaches to quality assessment in a variety of contexts. We describe their achievements and provide brief analyses through the lens of the framework above.